Aplicación móvil para los atractivos turísticos de la ciudad de Loja-Ecuador - González Auquilla, Julia de los Ángeles (2020)
The main objective of this research work is to create a mobile tourist app for Loja’s city, which would serve as a tool for tourism development, as well as being aimed at promoting the city's tourist attractions, For the development of this project, the tourist attractions of the city of Loja were investigated, of which 17 attractions were taken into account through the TripAdvisor platform subsequently the data compilation of the selected tourist attractions was carried out through the MINTUR Oct-2018 data sheets, for the implementation in the app besides complementary services such as hotels and restaurants were taken into account through the TripAdvisor and Booking platforms respectively, also the execution of surveys and interviews for the design of the mobile app, then wireframes were developed being the main structure of the application and mockups focusing on the visual identity of the final product and dissemination strategies were developed, based on the analysis and interpretation of survey results such as the promotion of the app on social networks of Facebook and Instagram; putting the application in two operating systems for the AppStore and Playstore platform and SEO positioning taken as a basic promotion strategy. Finally in essence, Loja has attractions as well as tourist and complementary establishments such as hotels and restaurants that can be exploited, through the development of the tourist activity and putting them in the mobile application because this means giving them to know and basic information on how to get there, activities that can be carried out, payment methods, as well as simplifying the time so the tourist can have a better experience at the time they visit the city. Key words: Tourist attractions, mobile application, tourism.